Mesenchymal Chondrosarcoma of the Mandible, a Big Dilemma: Report of a Rare Case in Mesenchymal Chondrosarcoma of the Mandible—Report of a Case With Discussion of Diagnostic and Therapeutic Dilemmas - Abbas Karimi; Samira Derakhshan; Farzaneh Mosavat; Zahra Gholamhoseini; Monir Moradzadeh Khiavi (Case Reports in Dentistry)
Chondrosarcomas are a group of malignant neoplasms with cartilaginous matrix production mostly found in flat and peripheral long bones. Mesenchymal chondrosarcoma is one of the most unusual and rare histological variants of chondrosarcoma, with a distinct histopathological appearance and biologically aggressive behavior. The amount of cartilage in mesenchymal chondrosarcoma may be so abundant that it is easily found in random sections or so scarce that numerous sections are required to discover it. In such cases, it is tough to make an accurate diagnosis, which leads to a big dilemma for pathologists and surgeons regarding diagnosis and treatment. Here, we report a mandibular mesenchymal chondrosarcoma in a 38-year-old male with a diagnosis of malignant small round cell tumor in incisional biopsy without any bone or chondroid formation. After ruling out lymphoma, a complete lesion excision was done. Diagnosis of mesenchymal chondrosarcoma was confirmed with small foci of chondroid material and strong positivity of tumoral cells for CD99 and S100. We highlight the fact that incisional biopsy frequently fails to provide sufficient tissue to establish the diagnosis of mesenchymal chondrosarcoma. Adequate tissue with multiple sections, detailed histopathological examination, and adjunctive IHC study are the keys to a definitive diagnosis.